A Study on the Advanced Logic State Diagnosis of Logic Lab-unit for Digital Education - Lee, Hyun-Chang; Lee, Kyu-Tae (International Journal of Engineering and Technology, 2018)
Background/Objectives: In this paper, a method to distinguish +3.3V logic state from the 4-level logic state (i.e., 0V, open, +5V and high-voltage) diagnosis circuit of the logic lab-unit was proposed.Methods/Statistical analysis: It is theoretically verified that the conventional logic state diagnosis circuit is difficult to distinguish the +3.3V logic state; the proposed method can distinguish logic state clearly.Findings: In order to verify the performance of the proposed method, the 6-chanel diagnosis circuit was set up to measure the output for each logic state. In the conventional method, it is possible to distinguish between open state and +3.3V logic state within the 0.43V under the ideal condition. However, it cannot distinguish them under the noisy condition.Improvements/Applications: On the other hand, the proposed method is measured 1.96V (i.e., increased by 455%) between the open state and the +3.3V logic state without affecting other states. In addition, the robustness of the measurement was verified in a noise environment. Since the proposed method is used by the microcontroller and analog multiplexer, it can be implemented with only one tri-state buffer or one transistor. Therefore, the proposed method is economically advantageous, as well.Â Â